Herramientas digitales interactivas como estrategia para el fortalecimiento de los aprendizajes con los estudiantes de sexto año de educación general básica de la escuela "Isabel la Católica", recinto Cuatro Esquinas, parroquia Guanujo, cantón Guaranda, provincia de bolívar, en el periodo junio- septiembre 2023. - Ávila Vásquez, Katerly Del Rocío (2023)
The objective of this current research endeavor is to consolidate the competencies of educators and students in the utilization of digital tools as a didactic strategy aimed at fortifying the learning experiences of sixth-grade students in general basic education at the "Isabel la Católica" school, situated in the cuatro esquinas district, Guanujo parish, Guaranda canton, Bolívar province, during the period spanning June to September 2023. This research is driven by the goal of enhancing the teaching process through digital tools, thereby generating components that facilitate a more comprehensive understanding of the learning materials by students. The research methodology employed in this endeavor is predominantly bibliographical, as it entails the acquisition of requisite information from the proposed variables during the document retrieval process. Furthermore, it follows a historical-logical approach through an examination of pertinent antecedents associated with the research question. It is deductive in nature, serving the purpose of implementing this digital learning environment, while concurrently being inductive by enabling the discernment of outcomes arising from the implemented application. The theoretical framework has been constructed through an exhaustive bibliographic search encompassing articles, books, journals, and online resources, serving as an authentic bibliographic foundation.